2019
DOI: 10.1257/pandp.20191013
|View full text |Cite
|
Sign up to set email alerts
|

A Reason to Wait: The Effect of Legal Status on Teen Pregnancy

Abstract: Although teen pregnancy has been on the decline in the United States, it remains among the highest within developed countries. Hispanics, who are more likely to be undocumented immigrants, lead this trend, yet the role of legal status has yet to be considered. To investigate this question, we examine teenage fertility responses to the Deferred Action for Childhood Arrivals (DACA) program, which provides temporary legal status to undocumented youth. We find that DACA reduced the likelihood of having a teenage b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In particular, AppendixTable A.6 shows that men substituted towards schooling from work and idleness, while women entirely substituted from idleness, perhaps due to a lower incidence of teenage births(Kuka, Shenhav and Shih, 2019).30 Further, in results not reported, we find that states with a higher deportation risk do not have a lower "legal premium," which could offset the response to deportation risk.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…In particular, AppendixTable A.6 shows that men substituted towards schooling from work and idleness, while women entirely substituted from idleness, perhaps due to a lower incidence of teenage births(Kuka, Shenhav and Shih, 2019).30 Further, in results not reported, we find that states with a higher deportation risk do not have a lower "legal premium," which could offset the response to deportation risk.…”
mentioning
confidence: 57%
“…We also contribute to a growing literature on the impacts of DACA, which finds that DACA improves health among children and adults (Hainmueller et al, 2017;Giuntella and Lonsky, 2018), reduces teenage pregnancy (Kuka, Shenhav and Shih, 2019), and improves adult labor market outcomes (Pope, 2016; Amuedo-Dorantes and Antman, 2017). Closer to this paper, Pope (2016), Amuedo-Dorantes and Antman (2017), and Hsin and Ortega (2017) analyze impacts on school attendance, focusing on older populations that have already completed high school, and therefore are already eligible for the program.…”
Section: Introductionmentioning
confidence: 92%
“…For infant mortality, one study did not observe an association with state-level expansion of PRWORA eligibility [ 22 ], while another observed that expansion to services under the Citizen/Alien Waived Emergency Medical policy was associated with a decrease in infant mortality [ 24 ]. For the remaining birth outcomes, inclusive policies (Citizen/Alien Waived Emergency Medical policy or DACA) were associated with better birth outcomes, including increased detection of poor fetal growth [ 25 ] and fewer births to adolescent mothers [ 26 ], or had null findings (infant birth injury [ 25 ]).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, Kuka et al (2020) find that DACA significantly increased high school attendance and high school graduation rates. There is also increasing evidence that DACA improved mental health (Venkataramani et al, 2017;Giuntella and Lonsky, 2020;Hainmueller et al, 2017;Patler et al, 2019;Giuntella et al, 2021) and birth outcomes (Hamilton et al, 2021), reduced teenage fertility (Kuka et al, 2019), and crime (Gunadi, 2020).…”
Section: Background 21 Deferred Action For Childhood Arrivals (Daca)mentioning
confidence: 99%